Analisis Semiotika Pada Poster Film “Vina: Sebelum 7 Hari” (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
This study aims to analyze the meanings embedded in the film poster "Vina: Sebelum 7 Hari" using Roland Barthes' semiotic approach. Film posters not only serve as promotional tools but also as powerful mediums for conveying complex messages to the audience. Through semiotic analysis, this research reveals the denotative, connotative, and mythological meanings of the visual elements in the poster. Primary data was obtained from direct observation of the film poster sourced from Dee Company's official website, while secondary data was collected through various relevant literatures and theories. The analysis results indicate that the visual elements in the poster effectively depict the essence of the story and the main conflict faced by the character in the film. This conclusion underscores that the "Vina: Sebelum 7 Hari" film poster is not only visually appealing but also effective in conveying the film's narrative and central themes to the audience